STRUCTURAL AND ADMINISTRATIVE FEATURES OF SETTLEMENTS IN GUZOR DISTRICT IN THE LATE 19TH – EARLY 20TH CENTURY (Journal of Multidisciplinary Sciences and Innovations, 2025)
This study analyzes the formation, administrative, and structural features of settlements within the Guzor district in the late 19th and early 20th centuries. The focus is placed on the network of amlaks, villages, and towns that existed during this period, as well as on the settlement patterns and administrative systems. Drawing on historical sources and archival documents, the research highlights the role of settlements in the district's socio-economic life and their strategic and administrative importance. This analysis contributes to a better understanding of local governance, the function of amindars (amlak governors), and the historical development of population centers.